Dampak Penggunaan Gadget terhadap Tingkat Fokus Belajar pada Anak Sekolah - Hasnah; Tutik Agustini; Ernasari; Rizqy Iftitah Alam; Idelriani (Window of Nursing Journal, 2025)
Gadgets are sophisticated tools with a variety of applications that can provide news media, social networks, interests, and even entertainment. Pre-primary school age should not be given independently. The use of applications that are not age-appropriate will have a negative impact. This study aims to determine the effect of using gadgets on the level of learning focus at UPT SD Negeri 4 Bila, Sidenreng Rappang Regency. The research design in this study was pre-experimental with one group pretest and posttest without control approaches. The research population is 82 people and the sample is taken using the total sampling method. This study used an independent t-text statistical test with a significance level of ρ< (α=0.005). The results showed that there was an effect of using gadgets on the level of focus on children's learning at UPT SD Negeri 4 Bila, Sidenreng Rappang Regency (ρ=0.040). The conclusion from this study is that there is an effect of using gadgets on the level of focus on children's learning at UPT SD Negeri 4 Bila, Sidenreng Rappang Regency. Therefore, through this study students are advised not to use gadgets frequently because it can reduce the level of focus on learning.